Comparative Analysis of Post-operative Pain Relief and Healing Outcomes between Single-Visit and Multiple-Visit Root Canal Therapy: A Tertiary Care Study - Miriyala Chaitanya; Abhilasha Bhawalkar; Anandamoy Bagchi; Divyatammana; Anshuman Shetty; Hitesh Chohan; Mohammed Mustafa (Wolters Kluwer Medknow Publications, 2024)
Background: Apical periodontitis and irreversible pulpitis are typical dental conditions treated with "Root Canal Treatment (RCT)". Single-visit RCT has become a viable alternative to the multi-visit RCT method used in traditional RCT. Methods: A total of 100 RCT participants were randomised to either the single-visit or multiple-visit groups at random. A "Visual Analogue Scale (VAS)" was used to measure post-operative discomfort at 24, 48, and 72 hours. At 6 and 12 months, peri-apical radiographs were used to assess the healing results. Results: At all time periods, there were no discernible variations in post-operative discomfort between the single-visit and multiple-visit groups. In contrast to the multiple-visit group, the single-visit group had greater rates of full healing at both 6 and 12 months. Conclusion: Compared to multiple-visit RCT, single-visit RCT provides similar post-operative pain alleviation and may result in better healing results. This suggests that single-visit RCT is a feasible and effective management option for patients who need root canal therapy.